Nanoplastics: From Separations to Analysis—Challenges and Limitations - Justyna Ośko; Kornelia Kadac-Czapska; Katarzyna Jażdżewska; Natalia Nowak; Piotr Kowalczyk; Małgorzata Grembecka (Separations)
The issue of nanoplastics (NPs) in the environment, following that of microplastics (MPs), is receiving increasing attention in the scientific community. Due to their size, these particles require the development and application of new methods for both quantitative and qualitative determination. Consequently, techniques commonly used for analyzing MPs may prove ineffective in the context of NPs. Isolating NPs from samples with complex matrices poses a significant challenge that directly affects analytical outcomes. This paper aims to discuss the main challenges encountered during the analysis of NPs in environmental samples. Various methods for the visualization and identification of NPs are examined, with a focus on microscopic, spectroscopic, and thermal techniques. The advantages and limitations of analytical approaches reported in the literature are summarized, offering guidance for the future development and standardization of methods used to determine NPs in environmental contexts.